Forging a glorious past via the 'present perfect': A corpus-based CDA analysis of China's past accomplishments discourse mediat(is)ed at China's interpreted political press conferences. (August 2018) - Gu, Chonglong
Highlights: The interpreted English discourse is central to global news production. The interpreted English discourse represents China's global "voice". The interpreters serve to (re)construct China's discourse and image. The interpreters' discursive mediation is vital in an increasingly mediat(is)ed world. Abstract: With increasing attention on discursive power, the "proper telling of China's story" ( jianghao zhongguo gushi ) has recently become a key slogan in mainland China. Held within the sociopolitical context of reform and opening-up, the televised and interpreter-mediated premier's press conferences constitute such a discursive event that facilitates the articulation of China's discourse to domestic and international audiences. This corpus-based CDA study explores how China's discourse on its past actions and accomplishments is mediated by government interpreters cross-linguistically in China's global voice — English. Through investigating the concordance lines containing the top 3 self-referential items ( we / China / government ), the use of present perfect (continuous) structures is established as a prominent feature in (re)presenting Beijing's achievements in English. Critical comparisons with the Chinese originals suggest the interpreters' proliferated use of these structures, which discursively leads to a stronger level of accomplishment, positive self -portrayal and, resultantly, political legitimisation. This interdisciplinary study highlights the interpreters' often neglected yet vital agency in further legitimating and (re)constructing China's image as important (re)tellers of "China's story" beyond national borders. This is particularly the case, given the mediat(is)ed and (re)mediat(is)ed nature of the high-profile event.